The profit maximising pricing model - Jackson, Cecil Wilfred (Rhodes University, Faculty of Commerce, Department of Accounting, 1988)
Writing thirty-five years ago, R S Edwards (1952) noted that as an economist who was once an accountant he had "been following with some perplexity the recent controversy in this country (United Kingdom) and the United States on the influences determining prices in manufacturing industry" (p 298). He explained that he was surprised that economist s should fin d the practice of cost-plus pricing "a significant discovery" (p 298) and that he was also surprised that "the existence of these procedures should have led to serious questioning of the validity of the marginal approach in economic analysis" (p 298). He observed that ru les of thumb are sometimes used in practice and commented "that these rules of thumb are 2 not always as satisfactory as they might be and sometimes they are downright stupid. But it surely does not follow that, because mistakes are sometimes made in business practice, the marginal analysis, which is merely a method of stating formal qualities of sensible behaviour, is inapplicable as a general approach" (p 298). Thirty-five years later, as an accountant who was once a student of economics, and noting the extent to which some economists have gone in absorbing the managerial and behaviourial schools into their theory of the firm, I am now especially surprised at the ease with which accountants, both professional and academic, dismiss the applicability of the marginalist approach . Using analytical techniques, this study will examine the accountant's pricing theories and the factors influencing the accountant when he makes a pricing decision and will compare the accountant's marginalist approach to the economic theory from which it is derived and examine the validity of the reasons given in accounting theory for the widespread exclusion of the application of the profit maximizing pricing decision model.
Keywords: Profit -- Mathematical models; Pricing -- Mathematical models